(untitled) (Revista Argentina de Cirugía, 2026)
Background: Retroperitoneal tumors are uncommon, and their surgical removal poses a challenge for surgeons, as the space where they develop contains major blood vessels that are often compressed or displaced by the tumor. Sarcomas are the most common retroperitoneal tumors. Objective: The aim of this study was to evaluate the short-term outcomes of surgical resection for retroperitoneal tumors. Material and methods: We conducted an observational, retrospective and descriptive study. The medical records of patients who underwent surgery between January 2005 and December 2024 were reviewed. The demographic, clinical and operative variables were analyzed. Results: A total of 12 patients underwent surgery; 8 had malignant lesions, 7 of which were sarcomas. There were no deaths in the series and 4 patients developed in 4 cases (33%). Mean length of hospital stay was 6.5 days. An R0 resection confirmed by pathological examination was achieved in 9 patients. Three patients who could be followed up developed tumor recurrences. Conclusion: Sarcomas were the most common retroperitoneal tumors. An R0 resection was achieved in most cases, with complication rates comparable to those reported in other series.